2022
DOI: 10.1002/14651858.cd013387.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy and cost-effectiveness of tests for codeletion of chromosomal arms 1p and 19q in people with glioma

Abstract: Diagnostic test accuracy and cost-effectiveness of tests for codeletion of chromosomal arms 1p and 19q in people with glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 150 publications
0
12
0
Order By: Relevance
“…PSENEN expression levels were significantly increased in astrocytomas compared to oligodendrogliomas ( Figures 3A,B ) and further increased along with grade II to III progression ( Figures 3C,E ). IDH mutation and 1p/19q codeletion are unique and are clinically significant molecular features in low-grade gliomas ( Dono et al, 2021 ; McAleenan et al, 2022 ). We, therefore, investigated the relationship between PSENEN expression level and the status of IDH mutation and 1p/19q codeletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSENEN expression levels were significantly increased in astrocytomas compared to oligodendrogliomas ( Figures 3A,B ) and further increased along with grade II to III progression ( Figures 3C,E ). IDH mutation and 1p/19q codeletion are unique and are clinically significant molecular features in low-grade gliomas ( Dono et al, 2021 ; McAleenan et al, 2022 ). We, therefore, investigated the relationship between PSENEN expression level and the status of IDH mutation and 1p/19q codeletion.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical analysis showed that PSENEN expression levels were higher in astrocytomas, high-grade tumors, IDH wildtype, and 1p/19q wildtype tumors than in their corresponding phenotype. These clinical features associated with high PSENEN expression levels are all correlated with poor clinical outcomes ( McAleenan et al, 2022 ). Therefore, it was concluded that elevated expression of PSENEN was strongly associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the review was published in the Cochrane Database of Systematic Reviews [ 20 ], and the review was undertaken and reported following Cochrane's guidance (which is consistent with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses [PRISMA]) [ 21 ]. A more detailed account of the methods and results can be found in the full Cochrane publication [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 Data Extraction Table, from Hanna et al [13] Figure 3 Cost Extraction Table, from Hanna et al [13] Figure 4 Example of decision tree model. Figure from McAleenan et al (2022) [17]…”
Section: Declarationsmentioning
confidence: 99%
“…A review to assess diagnostic test accuracy and cost-effectiveness of tests for codeletion of chromosomal arms 1p and 19q in people with glioma was included as part of the programme grant [17]. As such, this review assessed the diagnostic test accuracy (in terms sensitivity and speci city) for each of the tests.…”
Section: Economic Decision Model Case Study -Taken From Mcaleenan Et ...mentioning
confidence: 99%